Peranan Dinasti Fatimiyah Dalam Penyebaran Agama Islam di Asia Barat Daya Pada Abad IX - Densi Syahban Siregar; mohammad syawaludin; Padila Padila (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2021)
This study discusses the role of the Fatimid dynastyin the spread of Islam in Southwest Asia in the ninth century. This research uses descriptive qualitative research method and also heuristic research. The Fatimids were the Isma'iliyah Shi'ite dynasty. The Fatimid dynasty was founded by Ubaidillah al-Mahdi. Ubaidillah al-Mahdi is a person from the Syrian nation to North Africa. The concept used is the radical Shia Isma'iliyah withits doctrines that have political, religious, philosophical, and social dimensions. Based on the results of research and discussion, it is concluded that the role of the Fatimid dynasty in spreading Islam occurredin Egypt, North Africa, Sicily, the Red Sea Coastof Africa, Palestine, Syria, Yaman and the Hijaz which spread the Shi'a sect. The greatest progress made by the Fatimid dynasty was in the system of government, economics and science. The main objective of the Fatimid dynasty was to establish a new capitalcity, namely Cairo, to foster funds to establish alarge Islamic University, namely Al-Azhar and to disseminate the ideology of the Fatimid dynasty, namely, Shi'ism to Palestine, Syriaand Hijaz.